Encyocratella olivacea Strand, 1907, a senior synonym of Xenodendrophila gabrieli Gallon, 2003 (Araneae: Theraphosidae: Stromatopelminae) with a description of the male - Gallon, Richard C. (Zootaxa, 2005)
Encyocratella Strand, 1907 is removed from the synonymy with Chaetopelma Ausserer, 1871, and proposed as a senior synonym of Xenodendrophila Gallon, 2003. As a consequence, the secondary homonymy between Chaetopelma olivaceum (C. L. Koch, 1841) and Chaetopelma olivaceum (Strand, 1907) is rejected. Chaetopelma strandi Schmidt, 1991, previously applied as a nomen novum for Chaetopelma olivaceum (Strand, 1907), is treated as a junior synonym of Encyocratella olivacea Strand, 1907. Xenodendrophila gabrieli Gallon, 2003 is also considered a junior synonym of E. olivacea Strand, 1907 and the male is described for the first time.